a=(3/√5-√2)-(√5-√2)+2^-1-3^-2× (0.(3)^2
B=(1/2√5+2/√5+3√5/5)×(-33/2√2)
Răspunsuri la întrebare
Răspuns de
0
A=(3/√5-√2)-(√5-√2)+2⁻¹- 3⁻²× (1/3)²= 3/√5-√2-√5+√2+2⁻¹- 3⁻²× (1/3)²=
= 2/√5+ 1/2- 1/9× 1/9= 2/√5+ 1/2- 1/81=2/√5-79/162
B=(1/2√5+2/√5+3√5/5)×(-33/2√2)=(√5/10+2√5/5+3√5/5)×(-33√2/4)= =(√5/10+4√5/10+6√5/10)×(-33√2/4)= 11√5 /10×(-33√2/4)= - 363 / 40
= 2/√5+ 1/2- 1/9× 1/9= 2/√5+ 1/2- 1/81=2/√5-79/162
B=(1/2√5+2/√5+3√5/5)×(-33/2√2)=(√5/10+2√5/5+3√5/5)×(-33√2/4)= =(√5/10+4√5/10+6√5/10)×(-33√2/4)= 11√5 /10×(-33√2/4)= - 363 / 40
Alte întrebări interesante
Limba română,
8 ani în urmă
Chimie,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă